Biofuel production and soil GHG emissions after land‐use change to switchgrass and giant reed in the U.S. Southeast. (10th December 2017) - Nocentini, Andrea; Field, John; Monti, Andrea; Paustian, Keith
Abstract: United States mandated the production of biofuel from lignocellulosic feedstocks. Nonetheless, the cultivation of these feedstocks may produce debates, as agricultural land is scarce and it is primarily needed for food production and grazing. Thus, it is thought that biofuel production should be placed on land with low economical value (i.e., marginal land). At the same time, depending on what land is considered marginal and therefore available for lignocellulosic crops, different greenhouse gas impacts will be generated upon land use change. Here, we attempted to estimate the biomass production and soil greenhouse gas emissions of the cultivation of switchgrass ( Panicum virgatum L.) and giant reed ( Arundo donax L.) in the U.S. Southeast, when converting distinct former land uses. We employed the NLCD and the SSURGO databases to select grasslands, shrublands, and marginal croplands and to then allocate switchgrass and giant reed on this land basing on biophysical parameters included in the Land Capability Classification. After calibration, the DAYCENT model was employed to simulate 15‐year cultivation of both crops in the U.S. Southeast. Florida, Georgia, Mississippi and South Carolina were the States with the highest availability of land, thus the highest potential for biofuel production. Among scenarios, the one converting poor grazing land and marginal croplands yielded the greatest benefits: converting 3.6 Mha of land, 44 Mt/year of dry biomass could be produced, storing 0.05 Mt/year of soil organic C at the same time. In this scenario, considering 80‐km supply areas, nineteen biorefineries could deliver 7, 124 Ml/year of advanced ethanol across the region. When minimizing giant reed invasion risks through reallocating giant reed outside flooded areas, 4, 695 Ml/year of advanced ethanol could be still delivered from thirteen biorefineries, but the scenario turned in a biogenic greenhouse gas source (3.2 Mt CO2 eq/year). Abstract : Potential biofuel production and soil GHG emissions of the land‐use change to perennial switchgrass and giant reed in the U.S. Southeast was estimated through a simulation study. Both grazing land and marginal croplands were converted in distinct scenarios. The conversion of biophysically poor grazing land and marginal croplands combined in one scenario yielded the greatest benefits in terms of biofuel production (nineteen potential biorefineries) and GHG emissions (positive SOC storage); giant reed showed a higher potential for GHG mitigation than switchgrass.